Aplicações Over-the-Top de comunicações sociais e conteúdos audiovisuais – uma perpectiva tributária: estudo sobre a possibilidade de tributação das Aplicações Over-the-Top pelo ICMS e o ISS - Saran, José Eduardo de Paula (2019)
The technological evolution, in terms of physical equipment, the advent of the internet and then the so-called streaming technology, made possible the emergence of new media and platforms for the communication and transmission of audiovisual content that fit into the so-called Over-the-Top Services or Applications. This has occurred in parallel with a convergence of platforms and technologies in the field of social media and information and entertainment. Such services or applications have been competing with traditional means of message delivery and audiovisual content. They are assuming an increasingly important role as tools for social communication and for the dissemination of data, news, advertising, music, images, videos and audiovisual information or entertainment programming. The present dissertation aims to explain what they are and what consist the so-called Over-the-Top Applications, its history in Brazil and in the world, the technical and technological development that allowed its emergence, its social and economic importance, its legal nature, their classification into several species and, finally, if they can be or not achieved by taxation in Brazil. Only two species, which we call Social Communications and Audiovisual Content, will be studied in the genre Over-the-Top Applications. From the tax point of view, our cut will be to verify whether or not such Applications can be achieved, in the current configuration of the National Tax System, by the two most important current taxes of consumption, which are the ICMS (at its tax cores called ICMS-Commodity and ICMS-Communication) and the ISS. The choice is due to the fact that, in recent years, new conflicts of competence have arisen between the two taxes, a situation that Over-the-Top has caused or has intensified. At the end, the various doctrinal and jurisprudential positions on the main theme will be presented